2007
DOI: 10.1097/01.jto.0000268676.79872.9b
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and HER2 Gene Copy Number and Response to First-Line Chemotherapy in Patients with Advanced Non-small Cell Lung Cancer (NSCLC)

Abstract: This study suggested that EGFR expression and gene copy number, HER2 gene copy number, and P-Akt expression are not associated with response to first-line chemotherapy in NSCLC. Prospective phase III trials should compare standard chemotherapy with a TKI in selected NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 43 publications
(59 reference statements)
2
56
0
2
Order By: Relevance
“…[30][31][32] Preoperative evaluations include examination of one of the following specimens: bronchial brushings, bronchial washings, fine-needle aspiration (FNA) biopsy, core needle biopsy, endobronchial biopsy, and transbronchial biopsy. The mediastinal lymph nodes are also sampled to assess the staging and therapeutic options.…”
Section: Pathologic Evaluation Of Lung Cancermentioning
confidence: 99%
“…[30][31][32] Preoperative evaluations include examination of one of the following specimens: bronchial brushings, bronchial washings, fine-needle aspiration (FNA) biopsy, core needle biopsy, endobronchial biopsy, and transbronchial biopsy. The mediastinal lymph nodes are also sampled to assess the staging and therapeutic options.…”
Section: Pathologic Evaluation Of Lung Cancermentioning
confidence: 99%
“…Surprisingly, overexpression is associated with lower stage and grade of tumor [182]. Interestingly, there is an association of HER2/neu overexpression with NSCLC resistance to chemotherapy [183][184][185][186][187][188][189][190][191], which may account for the fact that HER2/neu overexpression is associated with a poor prognosis [35,[160][161][162][163][164][165][166][167][168][169][170][171][172][173] despite the association of HER2/neu overexpression with lower stage and grade. There is evidence for cooperativity and co-expression of HER1/EGFR [192], potentially associated with poorer prognosis [161,169,193], and there is data to support overexpression of HER2/neu as a mechanism for resistance to antibody inhibition of HER1/EGFR [194].…”
Section: Lungmentioning
confidence: 99%
“…Of the EGFR family of proteins, the expression of HER3 and/or HER2 has been shown to affect responses to EGFR-targeted drugs both in vitro and in vivo (13)(14)(15). A secondary EGFR mutation, T790M, has been identified that emerged after EGFR-TKI treatment (16)(17)(18), whereas K-ras mutations have been reported to be linked to primary resistance to EGFR-TKIs (19,20).…”
Section: Introductionmentioning
confidence: 99%